From neighbour to member: Assessing Moldova’s EU membership perspectives - Longhurst, Kerry (Intersections. East European Journal of Society and Politics, 2024)
This article examines Moldova’s prospective membership in the European Union (EU) in the wake of the EU’s renewed enlargement drive which was prompted by Russia’s 2022 invasion of Ukraine. It explores the dynamics shaping Moldova’s accession path, spotlighting obstacles to integration that official reports appear to overlook or underplay. The article compares EU and Moldovan documents, civil society reports, and insights from interviews with Moldovan officials and civil society representatives to gain a nuanced picture of the evolving situation. Attention is also given to the distinct characteristics of the currently unfolding enlargement process, including its sense of urgency and geopolitical significance which have led to calls for an expedited or ‘fast-track’ accession. Findings note that despite Moldova’s impressive progress in aligning with EU standards in many areas, substantial hurdles in justice reform, combating corruption and de-oligarchisation persist. Incomplete public administration reforms, uneven civil society involvement in decision-making, and issues associated with the Transnistria conflict also have consequences for Moldova’s EU prospects, especially if an expedited version of enlargement occurs.